2011
DOI: 10.1007/s00024-011-0320-4
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Coupling of Fluid-Filled Granular Material Under Shear

Abstract: Abstract. The coupled mechanics of fluid-filled granular media controls the physics of many Earth systems such as saturated soils, fault gouge, and landslide shear zones. It is well established that when the pore fluid pressure rises, the shear resistance of fluid-filled granular systems decreases, and as a result catastrophic events such as soil liquefaction, earthquakes, and accelerating landslides may be triggered. Alternatively, when the pore pressure drops, the shear resistance of these geosystems increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 64 publications
3
90
2
Order By: Relevance
“…Also, owing to our model of this drainage, we can identify several modes of liquefaction, from fluid-flow-induced 'fast settlement' to localized water film formation at permeability boundaries, to flow-induced liquefaction of low permeability layers that overly a high permeability layer, and even potentially thermally induced liquefaction when permeability is very low. In each of these example cases, we do not attempt to couple the behaviour of the grains to that of the water, or provide time-varying dynamic solutions, as no large-scale continuum model is available for grain-fluid interaction behaviour comparable in quality to the DEM model of [7]. Our intention in this paper has been to highlight the importance of fluid flow and spur an understanding of the need to develop soil models that can account for flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, owing to our model of this drainage, we can identify several modes of liquefaction, from fluid-flow-induced 'fast settlement' to localized water film formation at permeability boundaries, to flow-induced liquefaction of low permeability layers that overly a high permeability layer, and even potentially thermally induced liquefaction when permeability is very low. In each of these example cases, we do not attempt to couple the behaviour of the grains to that of the water, or provide time-varying dynamic solutions, as no large-scale continuum model is available for grain-fluid interaction behaviour comparable in quality to the DEM model of [7]. Our intention in this paper has been to highlight the importance of fluid flow and spur an understanding of the need to develop soil models that can account for flow.…”
Section: Resultsmentioning
confidence: 99%
“…In [7], a two-dimensional DEM model was coupled to a continuum model for fluid flow, and the interactions of grains and fluid were calculated for a sample of a few thousand grains. Their conditions are typical of 200 m-to 2 km-deep thin deposits sheared at ord(1) to ord (10) which are relevant for fault gouge conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid can be explicitly considered by expressing this law in terms of total stress and fluid pressure, using Equations (8,9) which leads to a formulation corresponding to Terzaghi's 1936 effective stress formulation [77,78]:…”
Section: Physical Explanation Of the Experimentsmentioning
confidence: 99%
“…However, the idea of putting them together via a system of deformable porous medium with a fluid flow makes the phenomena even harder to understand. Rapid changes in the porosity of the medium due to fluid flow, channeling and fracturing via momentum exchange with the flow make understanding the mechanics of the system a challenge [6][7][8][9]. Hydraulic fracturing of the ground is a good example for this coupled behavior of solid and fluid phases.…”
Section: Introductionmentioning
confidence: 99%
“…In the mechanics of porous media composed of a rigid skeleton, the diffusion timescale is negligibly small for incompressible interstitial fluids, 23 but when the medium is composed of loose grains, authors 19,24,25 have suggested that bulk compressibility gives rise to pore pressure diffusion even though the interstitial fluid is incompressible, as is obvious in Fig. 2.…”
Section: B Jamming As An Explanation Of Stick-slip Motionmentioning
confidence: 99%